An Analytical Framework to Investigate Groundwater‐Atmosphere Interactions Influenced by Soil Properties - Anastasia Vogelbacher; Milad Aminzadeh; Kaveh Madani; Nima Shokri (Water Resources Research)
Abstract The interaction between climate and groundwater forms a complex, coupled system that affects land‐atmosphere feedback processes and thus local climatic parameters. We propose an analytical framework that integrates local groundwater information and soil hydrophysical characteristics to identify regions with bidirectional (two‐way) coupling where groundwater is influenced by climatic factors (e.g., precipitation) and may affect local climate (e.g., through surface fluxes). The framework capitalizes on the concept of the evaporation characteristic length to quantify the hydraulic connection of groundwater to the soil surface. To evaluate the framework, we calculate the maximum depth of hydraulic connection (Dmax) between groundwater and the soil surface in Hamburg, Germany. For regions with Dmax exceeding the groundwater depth (d), a bidirectional mode of coupling is defined, while Dmax < d implies a unidirectional coupling mode. Our results indicate that climate driven evaporation changes potentially alter the coupling between groundwater and climate depending on soil texture. Moreover, soil hydraulic properties and shallow groundwater tables could play a crucial role in shifting land‐atmosphere feedback processes by influencing the coupling mode. This research provides insights into the groundwater‐climate interactions under various climatic conditions and soil textures which could contribute to sustainable land‐use management practices, particularly in regions characterized by bidirectional coupling.